2009
DOI: 10.1002/bip.21309
|View full text |Cite
|
Sign up to set email alerts
|

Close mimicry of lung surfactant protein B by “clicked” dimers of helical, cationic peptoids

Abstract: A family of peptoid dimers developed to mimic SP-B is presented, where two amphipathic, cationic helices are linked by an achiral octameric chain. SP-B is a vital therapeutic protein in lung surfactant replacement therapy, but its large-scale isolation or chemical synthesis is impractical. Enhanced biomimicry of SP-B’s disulfide-bonded structure has been previously attempted via disulfide-mediated dimerization of SP-B1-25 and other peptide mimics, which improved surface activity relative to the monomers. Herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 67 publications
(82 reference statements)
1
21
0
Order By: Relevance
“…While the disulfide linkage is strained, it can clearly permit dimer helical splays and surface dependent helix orientation in surfactant lipids, in agreement with our proposed model (6). Additionally, recent work on lung surfactant peptoids, or peptide mimics, showed that the linkage of monomers by a rigid triazole moiety to form a dimer enhanced in vitro surface activity in a lipid film relative to its monomeric counterparts (16). This further supports the idea that close proximity of the 2 peptoid helices serves to stabilize nanosilo formation.…”
Section: L343 Importance Of Sp-b Nh2-terminal Insertion Sequencesupporting
confidence: 84%
“…While the disulfide linkage is strained, it can clearly permit dimer helical splays and surface dependent helix orientation in surfactant lipids, in agreement with our proposed model (6). Additionally, recent work on lung surfactant peptoids, or peptide mimics, showed that the linkage of monomers by a rigid triazole moiety to form a dimer enhanced in vitro surface activity in a lipid film relative to its monomeric counterparts (16). This further supports the idea that close proximity of the 2 peptoid helices serves to stabilize nanosilo formation.…”
Section: L343 Importance Of Sp-b Nh2-terminal Insertion Sequencesupporting
confidence: 84%
“…The main approaches toward functional mimicry of surfactant proteins have involved peptide fragment synthesis, limited dimerization of SP-B and its analogues, recombinant protein expression, and more recently, peptoid synthesis, the subject of our recent contributions in this field 19-24. Although a recombinant form of SP-C is available,25 it is not palmitoylated, and no recombinant form of SP-B has yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The search for practical applications also began toward the development of reagents that could facilitate the cellular delivery of nucleic acids26, 63, 64 and serve as molecular recognition and capture reagents for diagnostic tests 65. We also established collaborations with other laboratories to explore the inhibition of protein–protein interactions,66, 67 the development of vaccines,68 antimicrobial peptoids,69 and lung surfactant mimetic70 peptoids. Research continues today in these areas as we address fundamental problems in nanoscience, self‐assembly, polymer physics, protein mimicry, and molecular recognition 71…”
Section: Protein Mimetic Polymersmentioning
confidence: 99%